Effects of grape juice consumption on muscle fatigue and oxidative stress in judo athletes: a randomized clinical trial - Goulart, M. J. V. V.; Pisamiglio, D. S.; Möller, G. B.; Dani, C.; Alves, F. D.; Bock, P. M.; Schneider, C. D. (Anais da Academia Brasileira de Ciências, 2020)
Abstract: Physiological levels of reactive oxygen species (ROS) are important for intracellular and extracellular redox regulation in signaling and defense processes. Strenuous exercise can also contribute to this imbalance, and the muscle fatigue, evidenced by impaired strength or power generation, can be caused by various reasons, including oxidative stress. Antioxidants can prevent the formation of ROS by intercepting free radicals. Twenty judo athletes were included in this randomized, double-blind clinical trial into grape juice and placebo groups, and they consumed grape juice or placebo daily for 14 days in a crossover model. The outcomes were analyzed before and after combat simulations. The upper limb strength was higher in the grape juice group than in the placebo (p [group] = 0.003). The lipid damage levels were 10% higher in the placebo group (p [interaction] = 0.048). During the pre-exercise, the placebo group showed 19% more DNA damage than the grape juice group. The superoxide dismutase activity was 80% lower in the grape juice group (p [interaction] < 0.001). The consumption of grape juice can improve parameters of oxidative stress by reducing the lipid and DNA damage.